2014
DOI: 10.1523/jneurosci.1330-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

WlsProvides a New Compartmental View of the Rhombic Lip in Mouse Cerebellar Development

Abstract: Math1 is the defining molecule of the cerebellar rhombic lip and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 31 publications
5
79
0
Order By: Relevance
“…Pax6 and the molecular underpinnings of cerebellar development RL precursors express Pax6 and Atoh1 (Yeung et al, 2014). The knock-out of Atoh1 results in the loss of Pax6 expression and eliminates all cerebellar glutamatergic neurons (Machold and Fishell, 2005;Englund et al, 2006;Fink et al, 2006).…”
Section: A Spatial Role Of Pax6 In the Development Of Rl Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pax6 and the molecular underpinnings of cerebellar development RL precursors express Pax6 and Atoh1 (Yeung et al, 2014). The knock-out of Atoh1 results in the loss of Pax6 expression and eliminates all cerebellar glutamatergic neurons (Machold and Fishell, 2005;Englund et al, 2006;Fink et al, 2006).…”
Section: A Spatial Role Of Pax6 In the Development Of Rl Derivativesmentioning
confidence: 99%
“…In fact, earlier work found that Atoh1 ϩ cells rapidly emigrate from the RL and withdraw from the RL progenitor pool (Machold and Fishell, 2005). Based on our recent analysis of compartmentation in the RL, we speculated that another population of cells (those originating from the interior face of the RL; Wls ϩ /Pax6 ϩ cells) served to replenish the RL progenitor pool (Yeung et al, 2014). With Pax6 absent, a depletion of the neural progenitor pool has been described in the development of retina and cortex, as a result of precocious cell-cycle exit (Farhy et al, 2013) or shorter cell-cycle length (EstivillTorrus et al, 2002).…”
Section: Pax6 and The Rl-lineage Progenitor Poolmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucial cellular and molecular mechanisms are established mainly by the mouse cerebellum (11,13,14). Regional expression of transcription factors in the cerebellar rhombic lip and ventricular zone shapes the fate of the hindbrain neuroepithelial stem cells of the developing cerebellum (5,9,10,17,19). Developmental defects of the cerebellum are considered in relation to selected human neurological disorders (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely applied in studying neurogenesis, including the cerebellum (14,16,19). We examined the number, distribution and some phenotypes of newly generated cells in various cortical layers of the adult primate cerebellum after global brain ischemia with different duration.…”
Section: Introductionmentioning
confidence: 99%